Hubungan Desa Wisata dengan Peningkatan Pendapatan Masyarakat Lokal di Desa Alamendah Kecamatan Rancabali Kabupaten Bandung (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the impact of tourist villages on increasing the income of local communities in Alamendah Village, Rancabali District, Bandung Regency. The method applied is a quantitative approach with an ex post facto design, where the researcher observes the relationship between variables without intervention. Data were collected through questionnaires from 100 respondents who are individuals involved in tourist village activities. Data analysis was conducted using normality tests, Pearson correlation tests, and the coefficient of determination with the assistance of SPSS. The study shows that the condition of Alamendah Tourist Village is considered very good, supported by natural and cultural tourism potential, supporting facilities, and local community involvement in various tourism activities. Meanwhile, the local community's income in Alamendah Village has experienced positive development through the integration of the agricultural and tourism sectors. The regression analysis results show that the tourist village has a positive and significant effect on local economic growth, with a significance value of 0.000 < 0.05. The correlation coefficient of 0.956 indicates a fairly strong relationship, while the determination coefficient of 91.4% indicates that the tourist village contributes to the increase in local community income. The conclusion of this study indicates that Alamendah Tourist Village is related to the economic condition of the local community, particularly in terms of increasing community income.